Opsoclonus Myoclonus Syndrome Due to an Ovarian Teratoma: A Case Report and Review of Literature. (3rd July 2020) - Mahesh, Karthik Vinay; Bansal, Ramandeep; Naheed, Darakhshan; Tandyala, Naresh; Singh, Ramandeep; Takkar, Aastha
ABSTRACT: The importance of ovarian teratoma as a cause of opsoclonus myoclonus ataxia syndrome (OMAS) and other paraneoplastic syndromes continues to be underestimated. A strong suspicion and appropriate diagnosis remain keys to successful outcome of paraneoplastic OMAS with ovarian teratoma. We report a 14-year-old girl with paraneoplastic OMAS in association with an ovarian teratoma who improved completely following resection of tumour as well as immunotherapy and review the literature briefly.